Camptothecin exerts anti-cancer effects through FoxM1 Inhibition (Indian Journal of Biochemistry and Biophysics (IJBB), 2025)
Camptothecin (CPT) is primarily known for its anti-cancer effects through the inhibition of topoisomerase I. However, emerging studies suggest that CPT may exert broader effects by targeting other oncogenic pathways. In this study, we explore a novel mechanism by which CPT interacts with FoxM1, a critical transcription factor involved in cancer progression. Our in silico docking studies and fluorescence quenching assays demonstrated that CPT and its analogs stably bind to the DNA-binding domain (DBD) of FoxM1. This interaction was further supported by chromatin immunoprecipitation (ChIP) assays, which demonstrated a significant reduction in FoxM1 promoter occupancy and subsequent downregulation of its target genes upon CPT treatment. Electrophoretic mobility shift assays (EMSA) further confirmed that CPT disrupts the binding of purified FoxM1-DBD to its cognate DNA. Importantly, the combination of CPT with Thiostrepton, a known FoxM1 inhibitor, resulted in a marked enhancement of therapeutic efficacy, as evidenced by reduced clonogenic potential and increased apoptosis in cancer cells. The synergistic effect of this combination highlights the potential of CPT to amplify the effectiveness of FoxM1-targeted therapies. Our study elucidates a novel mechanism of action for CPT, expanding its therapeutic potential beyond topoisomerase I inhibition. The findings suggest that FoxM1 levels could be a critical determinant in optimizing CPT-based therapies, and combining CPT with FoxM1 inhibitors may provide a more effective treatment strategy for cancers characterized by FoxM1 overexpression.